Analisis Pengaruh Kepemimpinan Transformasional terhadap Kinerja Pegawai melalui Organizational Citizenship Behavior sebagai Variabel Intervening: (Studi pada Pegawai Dinas Kesehatan Kabupaten Pamekasan) - Siti Jumaisah; Abdul Fatah Fanani; Hadi Susanto (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Siti Jumaisah, 2025. Analysis of the Influence of Transformational Leadership on Employee Performance Through Organizational Citizenship Behavior (Study on Pamekasan Regency Health Service Employees.) Postgraduate Program, Wijaya Putra University, Surabaya. Based on its approach, this research is included in the type of explanatory research. The research sample was 51 respondents. The objectives of this study were 1) To test and analyze transformational leadership has an influence on the performance of Pamekasan District Health Office employees. 2) To test and analyze transformational leadership has an influence on the organizational citizenship behavior of Pamekasan District Health Office employees. 3) To test and analyze organizational citizenship behavior has an influence on the performance of Pamekasan District Health Office employees. 4) To test and analyze transformational leadership has an indirect influence on the performance of Pamekasan District Health Office employees through organizational citizenship behavior. The research results show that: 1) transformational leadership has no significant effect on the performance of Pamekasan District Health Office employees with an original sample value of 0.126. 2) transformational leadership has a significant positive effect on the organizational citizenship behavior of Pamekasan District Health Office employees with an original sample value of 0.506. 3) organizational citizenship behavior has a significant positive effect on the performance of Pamekasan District Health Office employees with an original sample value of 0.516. 4) transformational leadership has a significant positive effect on the performance of Pamekasan District Health Office employees mediated by organizational citizenship behavior with an original sample value of 0.261.